IMPLEMENTASI PERBAIKAN LAYANAN MENGGUNAKAN METODE ANALISIS BERTAHAN (SURVIVAL ANALYSIS) PADA PT MITRA NASIONAL KUALITAS - Taufik Djatna dan Ludfi Oki Arifianto (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2015)
ABSTRACT Keeping customer satisfaction are important thing to maintain customer loyalty by implementing Customer Relationship Management (CRM). CRM is the main objective to improve customer retention through improved customer satisfaction. Provide appropriate services to gain customer satisfaction. Given appropriate services based on customer ratings of the importance of the level of service variables. In addition, service evaluation is done by applying  the  method  of  survival  analysis,  information  on  the  decline  gets  customer satisfaction based on customer retention. The purpose of this study was to assess the variables that are important to customer service. Then, the implementation needed to build a recovery service is based on the 4P's of marketing aspects of the company. Research at the National Quality Partners, Ltd. Jakarta, show resulting in customers assess the reliability and security attributes of the service is very important variable. Decline in retention rates and survival rates as well as the slope indicates the level of danger that companies need to do a recovery service. recovery services performed by approaching the 4P's of marketing with services variables that are considered important. then be sorted by priority service which should be rectified by the company using the Analysis Hierarchy Process (AHP). Keywords: customer relationship management, survival analysis, service variable, 4P’s of marketing, AHP